Application of Organic Fertilizer Tithonia Plus to Control Iron Toxicity and Reduce Commercial Fertilizer Application on New Paddy Field - Hakim, Nurhajati; ., Agustian; Mala, Yanti (UNIVERSITY OF LAMPUNG, 2012)
Ferrous toxicity is a one of the problems most often found in lowland rice systems in tropical and sub-tropical regionespecially in new paddy field (NPF) on Ultisols and Oxisols. Flooding during rice growth creates a chemicallyreduced state in soils causing reduction of insoluble (Fe3+) to soluble (Fe2+) form even at excessive level. ExcessiveFe2+ uptake is eventually the main cause of iron toxicity. The purpose of this study was to find an appropriateformulation of organic fertilizer Tithonia plus (OFTP) to control the iron toxicity, reduce the application of commercialfertilizers (CF) and increase rice production at various ages of NPF. The field experiment was conducted in farmerfields in Sitiung, Koto Baru sub-district, Dharmasraya district of West Sumatra province. Experimental design usedwas a factorial 2 x 6 in a split plot design. The main plot (A), the age of the opening of NPF were: 0 year;and 2 years;Subplot (B) a formulation of OFTP were: 2 Mg Tithonia ha-1 + 75% of CF; 2 Mg Tithonia ha-1 + 5 Mg rice strawha-1 + 50% of CF; 4 Mg Tithonia ha-1 + 25% of CF and three treatmens without Tithonia i.e. 5 Mg rice straw ha-1 +75% of CF; 2 Mg animal cow manure ha-1 + 75% of CF, and 100% of CF. Liming with 500 kg CaCO3 ha-1were appliedfor all treatments. The results showed the use of OFTP increased the nutrients availability such as N, P, and K onNPF and control the iron toxicity. The appropriate formulation of OFTP to control the iron toxicity and reduced theapplication of chemical fertilizer for higher rice production at NPF were two options: (1) 2 Mg of Tithonia ha-1 + 5 Mgof rice straw ha-1 + 50% of commercial fertilizers; and (2) 2 Mg of Tithonia ha-1 + 75% of commercial fertilizers. In thiscase the reducing of commercial fertilizers application were 50% and 25%, respectively.[How to Cite: Hakim N, Agustian and Y Mala. 2012. Application of Organic Fertilizer Tithonia Plus to Control Iron Toxicity and Reduce Commercial Fertilizer Application on New Paddy Field. J Trop Soils 17: 135-142. Doi: 10.5400/jts.2012.17.2.135][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.2.135]